BIMBINGAN DAN PELATIHAN PEMBUATAN KOMBUCHA DARI BUAH NANAS DI DESA BATU BULAN KECAMATAN MOYO HULU KABUPATEN SUMBAWA - Afgani, Chairul Anam; Sari, Ratna Nurmalita; Nairfana, Ihlana; Setiawati, Veni Rori (Universitas Muhammadiyah Mataram, 2022)
Pinneaple is one of the major commodity in West Nusa Tenggara. This commodity could be processed into commercial product such as kombucha. Kombucha is fermented tea by using Simbiotic Culture of Bacteria and Yeast (SCOBY) which incubated for 14 days. During kombucha processing, fruit juice were diluted then added by sugar which involved as main microorganism nutrition in fermentation. This community development aimed to transfer the knowledge of kombucha making from pine and other domestic fruits. Product processing explanation, disscussion, and practice were conducted to transfer the complete knowledge for the target. The result showed that Batu Bulan community-as the target, could understand the kombucha making and figure its benefit out.